Dimensions of Social Media Logics: Mapping Forms of Journalistic Norms and Practices on Twitter and Instagram. Issue 7 (26th August 2020) - Hermida, Alfred; Mellado, Claudia
Abstract: More than a decade of research in journalism studies on social media has examined how journalists and news organizations have adopted and/or adapted to Twitter, Facebook, Instagram, and more, surfacing tensions over professional control and normalization. This article advances a conceptual framework for analyzing forms of journalistic norms and practices on social media that takes as its starting point the nature of its platforms, specifically Twitter and Instagram, proposing five analytical dimensions to investigate journalism on social media. They are: 1) structure and design; 2) aesthetics; 3) genre conventions; 4) rhetorical practices; and 5) interaction mechanisms and intentionality. The accounts of five Chilean journalists are used to illustrate how these five dimensions work in the two platforms.